Anaerobic capacity: Effect of computational method - Noordhof, D. A.; Vink, A. M. T.; de Koning, J. J.; Foster, C. (International Journal of Sports Medicine, 2011)
Anaerobic capacity (AnC) can be estimated by subtracting VO2 consumed from VO2 demand, which can be estimated from multiple submaximal exercise bouts or by gross efficiency (GE), requiring one submaximal bout. This study compares AnC using the MAOD and GE method. The precision of estimated VO2 demand and AnC, determined by MAOD using 3 power output - VO2 regressions, based on VO2 from min 8-10 (10 - Y), during min 4 without (4 - Y) and with forced y-intercept (4+Y), and from GE was evaluated by the 95% confidence interval (CI). Well-trained males (n=15) performed submaximal exercise tests to establish VO2 demand with the MAOD and GE method. To determine AnC subjects completed a constant power output trial. The 3 MAOD procedures and GE method had no significant difference for VO2 demand and AnC. The 4+Y MAOD procedure and GE method resulted in a smaller 95% CI of VO2 demand and AnC than the 10 - Y (p<0.05; p<0.01) and 4 - Y (p<0.001; p<0.01) MAOD procedures. Therefore, the 4+Y MAOD procedure and GE method are preferred for estimating AnC, but as individual differences exist, they cannot be used interchangeably.